Geometric Analysis of the Scaling of the Manganese Recovery Process Using Current Distribution and Potential Simulation Techniques - Esaú M. Rodríguez Vigueras; Victor E. Reyes Cruz; Felipe M. Galleguillos Madrid; José A. Cobos Murcia; Quinik L. Reyes Morales; Gustavo Urbano Reyes; Marissa Vargas Ramírez; Felipe Legorreta García; Marinka Varas (Metals)
Electrolytic metallic manganese (EMM) is used as an alloying metal to provide resistance to abrasion and corrosion. Highly pure EMM is obtained through electrorecovery or electrowinning. Efforts are ongoing to improve the efficiency and profitability of this process, as 85 to 90% of manganese is produced by the mining industry. This study applied computer-aided engineering (CAE) to provide information on the behavior of the potential distribution at the electrodes in cells separated by membranes, which allows for the optimization of the EMM production process. The experimental results obtained galvanostatically for EMM allowed for validation of the simulation parameters. It was determined that the cell with 11 compartments is more suitable compared to cells with fewer compartments, since it has lower oxidation-normalized current density and oxidation potential, which affect the distribution of cathodic potential in the process of obtaining EMM. The simulation highlighted a better distribution of the cathodic and anodic potentials due to the increase in the number of electrodes. This saves time and resources in the design of electrochemical cells with a greater number of compartments.